Gender Differences Influence Brain's Beta Oscillatory Responses in Recognition of Facial Expressions - Güntekin, Bahar; BAŞAR, EROL (ELSEVIER IRELAND LTD, ELSEVIER HOUSE, BROOKVALE PLAZA, EAST PARK SHANNON, CO, CLARE, 00000, IRELAND, 2007)
There are only few studies describing gender differences in recognition of facial expressions. Our study has the aim to analyze the effect of gender differences in oscillatory brain responses. Three sets of Ekman and Friesens's facial expressions (neutral, angry, and happy) were presented to 26 healthy subjects (13 men) while recording from 13 different scalp locations. Occipital beta response (15-24 Hz) was significantly larger for women than for men during the presentation of face expressions. Our results demonstrate that processing of emotional face expressions clearly differs between men and women. Accordingly, the results indicate the necessity of introducing standardization between male and female subjects by means of oscillatory dynamics. In turn, this standardization may be useful for cognitive and clinical studies. (C) 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: Gender Differences; Event Related Oscillations; Beta; Face Expressions; Visual Perception; Emotion; Sex Differences; Dynamics; Gamma; Integration; Potentials; Faces; Synchronization; Cinsiyet Farklılıkları; Olaya İlişkin Salınımlar; Yüz İfadeleri; Görsel Algı; Duygu; Seks Farklılıklar; Dinamik; Gama; Bütünleşme; Potansiyeller; Yüzleri; Senkronizasyon